Cancer Immunotherapy associated with Interstitial Lung Disease - João Costelha; Artur Barros (Sociedade Galega de Medicina Interna, 2020)
The field of oncology has entered an era of molecularly targeted therapy¹. Immunotherapy enhances the patient's immune system to fight disease and has recently been a source of promising new cancer treatments. Among the many immunotherapeutic strategies, immune checkpoint blockade has shown remarkable benefit in the treatment of a range of cancer types ² representing the latest major breakthrough in oncology and offer a new paradigm for the treatment of different types of advanced solid tumors³. Compared with cytotoxic chemotherapy, agents such as Crizotinib, an oral tyrosine kinase inhibitor, offer the promise of improved outcomes with fewer toxicities. However, these agents often target multiple pathways, it is important to recognize both on-target and off-target effects so as to anticipate and treat toxicities that arise⁴¯⁵. This report describes the clinical case of a 57-year-old man, ex-smoker, being treated with a tyrosine kinase inhibitor for a lung adenocarcinoma's recurrence. He was admitted to the emergency department for progressive (two weeks of evolution) dyspnea and a dry cough after the end of immunotherapy. Later, he was sent to an intensive care unit (ICU) due to severe respiratory insufficiency secondary to immunotherapy pneumonitis. In the medical image presented are visible extensive areas with depolyzed glass densification and thickening of interlobular septa with diffuse alveolar damage type formation, findings compatible with a toxic pneumonitis. The mechanisms that result in immune-related adverse events are still being elucidated. Some potential mechanisms include increasing T-cell activity against antigens that are present in tumors and healthy tissue, increasing levels of preexisting autoantibodies, an increase in the level of inflammatory cytokines². With adequate ventilatory support in the ICU, the treatment of pneumonitis was achieved with the use of high-dose steroids. Immunotherapy is becoming a standard approach for many cancer patients. Immune-checkpoint inhibitors can generate immune-related adverse events. Interstitial lung disease has been identified as a rare but serious and potentially deadly event requiring close monitoring and treatment. ³¯⁵